Antioxidant Stability of Edible Oil Using Rheological Behaviour and in vitro Analysis - RUBALYA VALANTINA*, S.; GAYATHRI!, K. (Asian Journal of Chemistry, 2010)
In food industry, rheological behaviour and thermal degradationare the important parameters required to determine the quality andstability of food system. In this paper, the rheological behaviour andthermal degradation of sunflower oil and palm oil, is investigated. TheNewtonian behaviour of the oils are studied from the kinematic viscosityof unused edible oils (sunflower oil, palm oil, groundnut oil, coconutoil, olive oil, sesame oil) using redwood viscometer at temperatures from30 to 90 ºC. Increase in viscosity of used (heated to frying condition,210 ºC) edible oils like sunflower oil, palm oil are studied in the samevariation of temperature shows the non-Newtonian behavoiur of theoils. This oxidation process can be prevented or retarded by the additionof synthetic or natural antioxidants. The antioxidant activities in oils onheating to smoke point are analyzed using in vitro studies. The freeradical scavenging activity of the samples using ABTSH and DPPH ismeasured and the antioxidant activity of sunflower oil is much effectivethan palm oil.